Comparison of the Non-Specific Binding of Unfractionated Heparin and Low Molecular Weight Heparin (Enoxaparin) to Plasma Proteins - Young, Edward; Cosmi, Benilde; Weitz, Jeffrey; Hirsh, Jack (Thrombosis and Haemostasis, 1993)
The non-specific binding of anticoagulantly-active heparin to plasma proteins may influence its anticoagulant effect. We used low affinity heparin (LAH) essentially devoid of anti-factor Xa activity to investigate the extent and possible mechanism of this non-specific binding. The addition of excess LAH to platelet-poor plasma containing a fixed amount of unfractionated heparin doubled the anti-factor Xa activity presumably because it displaces anticoagulantly-active heparin from plasma proteins. Although dextran sulfates of varying molecular weights also increased the anti-factor Xa activity, less sulfated heparin-like polysaccharides had no effect. These findings suggest that the ability to displace active heparin from plasma protein binding sites is related to charge and may be independent of molecular size. In contrast to its effect in plasma containing unfractionated heparin, there was little augmentation in anti-factor Xa activity when LAH was added to plasma containing low molecular weight heparin (LMWH), indicating that LMWH binds less to plasma proteins than unfractionated heparin. This concept is supported by studies comparing the anticoagulant activity of unfractionated heparin and LMWH in plasma with that in buffer containing antithrombin III. The anti-factor Xa activity of unfractionated heparin was 2-fold less in plasma than in the purified system. In contrast, LMWH had identical anti-factor Xa activity in both plasma and buffer, respectively. These findings may be clinically relevant because the recovered anti-factor Xa activity of unfractionated heparin was 33% lower in plasma from patients with suspected venous thrombosis than in plasma from healthy volunteers. The reduced heparin recovery in patient plasma reflects increased heparin binding to plasma proteins because the addition of LAH augmented the anti-factor Xa activity. In contrast to unfractionated heparin, there was complete recovery of LMWH added to patient plasma and little increase of anti-factor Xa activity after the addition of LAH. These findings may explain why LMWH gives a more predictable dose response than unfractionated heparin.